Influence of Mitomycin C on the Therapeutic Success of Stand-Alone Xen45 Gel Stents and Its Combination with Cataract Surgery in Open-Angle Glaucoma Patients - Denkel, Laura; Hohberger, Bettina; Lämmer, Robert (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Minimally invasive glaucoma surgery (MIGS), like Xen45 gel stents, is known as effective therapy in lowering intraocular pressure (IOP); however, fibrotic reactions are a common problem in postoperative management. It was the aim of this study to investigate the therapeutic success of Xen45 gel stents as a stand-alone technique (Xen) and combined with cataract surgery (XenPhaco), and with antimetabolites (mitomycin C, MMC) in open-angle glaucoma patients.Methods Retrospective analysis was performed of 199 eyes of 177 glaucoma patients of the Department of Ophthalmology, University of Erlangen Nürnberg, and from the Erlangen Glaucoma Registry (NCT00494923; ISSN 2191-5008, CS-2011) who underwent implantation of a Xen45 gel stent. Therapeutic success was defined as IOP reduction of ≥ 20% on the same or less anti-glaucomatous medication after 12 months compared to preoperative and without any additional glaucoma-related surgery (except bleb needling). IOP reduction, reduction in local anti-glaucomatous eye drops, and intra- and postoperative complications were monitored.Results Stand-alone Xen45 gel stent: therapeutic success was reached in 39% (–MMC) and 55% (+MMC). Failure rate was 61% (–MMC) and 45% (+MMC). XenPhaco: therapeutic success was achieved in 57% (–MMC) and 46% (+MMC). Failure rate was 43% (-MMC) and 54% (+MMC). Data were not different for group and subgroup analyses (p > 0.05).Conclusions The use of MMC seemed to increase the therapeutic success rate after stand-alone Xen45 gel stent implantation and combined with cataract surgery, yet statistical significant was not reached.
Keywords: MIGS; Xen Stent; glaucoma; IOP; MMC; fibrosis